Removal of amaranth dye over surfactant modified dull pink clay from aqueous medium. Issue 15 (8th December 2021) - Munir, Muhammad; Nazar, Muhammad Faizan; Zafar, Muhammad Nadeem
ABSTRACT: The focus of this study was to modify the low cost, environment friendly and abundantly available dull pink clay (DPC) with cetyltrimethylammonium bromide (CTAB, a cationic surfactant) in order to increase its adsorption capacity. Surfactant-modified clays are known to enhance the adsorption capacity of hydrophobic organic contaminants from aqueous solution owing to their increased organic content. Herein, we described the modification of DPC with CTAB to produce modified adsorbent (CTAB-DPC) and its application for adsorptive removal of amaranth (AM) dye from water. The surface morphology of CTAB-DPC was revealed using scanning electron microscopy (SEM). The Brunauer–Emmett–Teller (BET) surface area, pore volume and pore diameter of CTAB-DPC was found to be 271.85 m 2 /g, 0.464 cm 3 /g and 10.068 nm, respectively. The adsorption of AM on CTAB-DPC strongly followed the Langmuir and Dubinin-Radushkevich isothermal models; whereas the kinetics studies revealed that the adsorption process was better explained by pseudo second order. At all temperatures the values of Δ G° are negative (−14.06 to −14.98 KJ/mol and −20.654 to −21.997 KJ/mol for DPC and CTAB-DPC, respectively), which shows that adsorption of AM onto DPC and CTAB-DPC is feasible and spontaneous at all temperatures. The CTAB-DPC displayed remarkable efficiency towards the removal of widely used AM from aqueous system. The results revealed that the maximum removal efficiency ( 97%, 73 mg/g) was achieved at 0.5 g/L of CTAB-DPC dose, 50 ppm AM concentration, pH 2 and temperature 55°C, which suggests that CTAB-DPC could be an effective adsorbent that could easily be scaled-up into adsorption applications.